Rates of non-confounded HIV-associated neurocognitive disorders in men initiating combination antiretroviral therapy during primary infection. (January 2016) - Evering, Teresa H.; Applebaum, Allison; La Mar, Melissa; Garmon, Donald; Dorfman, David; Markowitz, Martin
Abstract : Objective: To determine the prevalence of HIV-associated neurocognitive disorders (HAND) in HIV-infected participants who initiated combination antiretroviral therapy (cART) during primary infection. Design: Cross-sectional observational study. Methods: HIV-infected men without neuropsychiatric confounds who had initiated cART during primary infection were administered a neuropsychological battery as well as questionnaires evaluating depression and quality of life. Eligibility was determined by a medical examination with history and review of records. Results: Twenty-six primarily non-Hispanic white (73%), male (100%) participants were enrolled and underwent neurocognitive assessment. Mean age was 43 (28–71) years, with a median of 17 years of education (13–24). Median current and nadir CD4 + T-cell counts were 828 (506–1411) and 359 (150–621) cells/μl. All participants had plasma HIV-1 RNA less than 50 copies/ml. Median duration of cART prior to enrolment was 5.7 years (2.2–9.9). Median global deficit score was 0.17 (0.00–0.60). Only one (4%) participant was impaired. Conclusion: Rates of HAND in this cohort of HIV-infected men without comorbid conditions who initiated early cART are low. Our findings suggest a possible neuroprotective benefit of early cART and an important contribution of comorbidities to observed HAND prevalence. Abstract : Supplemental Digital Content is available in the text